Peran Kepemilikan Manajerial dalam Memoderasi Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Manajemen Laba - I Gusti Agung Arista Pradnyani; Ni Luh Putu Widhiastuti (Jurnal Akuntan Publik, 2023)
This study aims to analyze the effect of profitability and company size on earnings management with managerial ownership as a moderating variable. The population in this study are Manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2019-2021. Samples on this research were taken using purposive sampling method and the number of samples used in this research is 25 companies. The results obtained in this study are profitability have a significant positive effect on earnings management, company size do not significantly influence earnings management, and managerial ownership can moderate the effect of profitability and company size on earnings management.